How to Speak the Truth According to Kierkegaard - Jacoby, Matthew G. (Sophia, 2023)
In this article, I examine Soren Kierkegaard's existential critique for truth-speaking. My contention is that this is more than a mere quest for sincerity in religious profession. Kierkegaard, rather, is concerned with the existential position that is inherent in the way a person confesses the doctrines of the Christian faith. I show how Kierkegaard uses his pseudonyms to problematise the issue of making religious truth claims and then I explain how Kierkegaard's notion of truth-speaking operates within his definition of the self as a process of relating. To speak the truth one must inhabit a particular existential situation and one's speaking must become part of an authentic process of becoming that is itself truth.